Federation's alternative tax constitutions and risky education - Panu Poutvaara (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
We analyze a two-period modell where risk-averse students divide their time between risky education, leisure, and work. The educated can migrate. Wagetax financed transfer to students acts as an insurance, and increases both investment in education and demand for leisure. We drive sufficient conditions for tax competition to lead to too low wage tax rates. We suggest, that the educated should pay their wage taxes to the region which has financed their education. We show that this would increase taxation and investment in education, and would benefit also the owners of the complementary factor.
Keywords: 330; Fiscal federalism; tax competition; optimal taxation; education subsidies; tax constitution; Bildungsinvestition; Arbeitsangebot; Bildungsökonomik; Ausbildungsfinanzierung; Finanzföderalismus; Lohnsteuer; Steuerwettbewerb; Internationale Arbeitsmobilität; Theorie